Green Marketing: Drivers in the Process of Buying Green Products—The Role of Green Satisfaction, Green Trust, Green WOM and Green Perceived Value - Román-Augusto, Jose Antonio (2022)
Green marketing is currently one of the most powerful strategies in the corporate world as it responds to a growing demand for green products. Therefore, this study aims to analyse the influence of green perceived value on green trust and green satisfaction, study how both variables impact green word of mouth in turn and, at the same time, how the three variables influence green purchase intention. Data collection was carried out through a digital survey of buyers of green products. The hypotheses posed were solved with a PLS-SEM model through the Smart-PLS software. The results showed that green perceived value positively affects green trust and green satisfaction. Furthermore, green satisfaction was found to influence green trust and green WOM. Green trust also influences green WOM. Regarding the antecedents of green purchase intention, only green satisfaction and green trust showed a positive relationship. In contrast, green WOM did not show a relationship with green purchase intention. The article shows the importance of green satisfaction for green companies in achieving green purchase intention, green WOM and green trust. Green perceived value is also an important variable, as it is the trigger for the process that leads to green purchase intention.